The autophagy GABARAPL1 gene is epigenetically regulated in breast cancer models. Issue 1 (December 2015) - Hervouet, Eric; Claude-Taupin, Aurore; Gauthier, Thierry; Perez, Valérie; Fraichard, Annick; Adami, Pascale; Despouy, Gilles; Monnien, Franck; Algros, Marie-Paule; Jouvenot, Michèle; Delage-Mourroux, Régis; Boyer-Guittaut, Michaël
Abstract Background The GABARAP family members (GABARAP, GABARAPL1/GEC1 and GABARAPL2 /GATE-16) are involved in the intracellular transport of receptors and the autophagy pathway. We previously reported thatGABARAPL1 expression was frequently downregulated in cancer cells while a highGABARAPL1 expression is a good prognosis marker for patients with lymph node-positive breast cancer. Methods In this study, we asked using qRT-PCR, western blotting and epigenetic quantification whether the expression of theGABARAP family was regulated in breast cancer by epigenetic modifications. Results Our data demonstrated that a specific decrease ofGABARAPL1 expression in breast cancers was associated with both DNA methylation and histone deacetylation and that CREB-1 recruitment onGABARAPL1 promoter was required forGABARAPL1 expression. Conclusions Our work strongly suggests that epigenetic inhibitors and CREB-1 modulators may be used in the future to regulate autophagy in breast cancer cells.